of, on, of Analysis of Law Enforcement Against Criminal Action on Illegal Fishing (Case Study of Mv Hai Fa) - Yusuf Nur Arifin (Fakultas Hukum Universitas Hang Tuah, 2020)
The MV Hai Fa case has taken the public's attention for almost the last 5 years after the court ruling was issued by the Ambon Court. MV Hai Fa was declared proven to have captured 15 tons of spike shark (Carcharhinus spp) and hammerhead shark (Sphyrna lewini) which are some of the protected species of marine animals as stated in the Minister of Maritime Affairs and Fisheries Regulation Number 59 of 2014 concerning Prohibition of Fish Expenditures Cowboy sharks (Carcharhinus spp) and hammerhead sharks (Sphyrna lewini) outside the territory of the Republic of Indonesia and violating Article 100 in conjunction with Article 7 paragraph (2) letter m law No. 45 of 2009 concerning amendments to Law No. 31 of 2004. This study uses normative legal research methods with a case, concept, law and comparison approach with the aim of knowing and analyzing the law enforcement process against illegal fishing cases by MV Hai Fa in Indonesian waters as well as analyzing comparative reviews of national law and international law in MV Hai Fa case and the government system owned by Vietnam and Australia. The results of the study concluded that the need for a government institution which is appointed by the President could carry out full coordination and supervision until the judicial process and that the revision of fisheries law which has more severe sanctions was adjusted to international law and the material and immaterial losses caused by the crime.